2012
DOI: 10.1002/uog.11067
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cervical elastography: a reproducibility study

Abstract: Objectives To assess a new method for numerical quantification of cervical elastography during pregnancy and to evaluate the repeatability of the measurements. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(157 citation statements)
references
References 15 publications
8
147
0
2
Order By: Relevance
“…According to the elastographic measurements, we found that the external part of the upper lip of the cervix was significantly softer than the internal part and lower lip in each group. This result was compatible with the results of Molina et al (13) who found that the superior and external regions of the cervix were significantly softer than the inferior and internal regions. However, we believe that this result may still be open to criticism.…”
Section: Discussionsupporting
confidence: 93%
“…According to the elastographic measurements, we found that the external part of the upper lip of the cervix was significantly softer than the internal part and lower lip in each group. This result was compatible with the results of Molina et al (13) who found that the superior and external regions of the cervix were significantly softer than the inferior and internal regions. However, we believe that this result may still be open to criticism.…”
Section: Discussionsupporting
confidence: 93%
“…опуб-ликовали похожие результаты, отметив, что самый плотный участок -внутренняя часть задней губы. Авторы полагали, что это связа-но с тем, что эти участки являются наиболее отдалёнными от датчика и, следовательно, на них применяется давление наименьшей силы, компрессия тканей бывает намного меньше по сравнению с тканями, локализованными в непо-средственной близости к датчику [12].…”
Section: таблицаunclassified
“…Большинство исследований эластичности шейки матки у беременных с нормальным те-чением беременности [10] и с высоким риском преждевременных родов [8,12] проведено в по-следнем триместре, в то время как в литературе отсутствуют данные об изменениях эластичнос-ти шейки матки в I триместре у женщин с хро-мосомной патологией плода.…”
Section: таблицаunclassified
“…The original article by Molina et al 1 3 , are justified and constitute a worthy input to the discussion. However, our team, carrying out diagnostic tests independently, adopted assumptions similar to those of Molina et al 1,4 ; using a vaginal probe, we marked a region of interest 1.0 cm in diameter on both anterior and posterior cervical lips ( Figure 1).…”
Section: Correspondence Quantitative Cervical Elastography In Pregnancymentioning
confidence: 99%
“…The original article by Molina et al 1 3 , are justified and constitute a worthy input to the discussion. However, our team, carrying out diagnostic tests independently, adopted assumptions similar to those of Molina et al 1,4 ; using a vaginal probe, we marked a region of interest 1.0 cm in diameter on both anterior and posterior cervical lips ( Figure 1). With respect to the pressure on the cervix, we followed the guidelines regarding the minimum conditions required to measure stiffness of tissue that were provided by the supplier of the ultrasound equipment (EUB 7500, Hitachi Medical Systems, Wiesbaden, Germany), along with the examination information displayed on the ultrasound screen 4 .…”
Section: Correspondence Quantitative Cervical Elastography In Pregnancymentioning
confidence: 99%